Teaching computer-assisted qualitative data analysis to a large cohort of undergraduate students - Roberts, Lynne; Breen, Lauren; Symes, Maxine (Routledge, 2013)
Qualitative research is increasingly being conducted with the support of computer-assisted qualitative data analysis software (CAQDAS), yet limited research has been conducted on integrating the teaching of CAQDAS packages within qualitative methods university courses. Existing research typically focuses on teaching NVivo to small groups of postgraduate (primarily doctoral) students and mostly take the form of reflections of the trainers. In 2011, we implemented the teaching and use of a CAQDAS package, NVivo, within a large third-year undergraduate psychology research methods unit. Sixty-seven students participated in an online survey evaluating the use of NVivo in the unit. In this paper, we present quantitative and qualitative findings related to students' perceptions of the resources provided, their confidence in using NVivo, their satisfaction with the teaching and their intentions to use CAQDAS in the future. Student evaluations were generally positive, but highlighted the need for both increased class time and greater access to the CAQDAS program outside of class time to enhance opportunities for learning.